Penguatan Kapasitas Komunitas Statistika Bantar dalam Tata Kelola Data Desa untuk Pembangunan Berkelanjutan - Adnan, Arisman; Yolanda, Anne Mudya; Erda, Gustriza; Syamsudhuha, Syamsudhuha; Indra, Zul; Solfitri, Titi; T, Masrina Munawarah (Unri Conference Series: Community Engagement, 2024)
This activity aims to strengthen the capacity of the statistical community in Bantar Village in supporting the transformation and management of data for sustainable development. The program focuses on assisting village officials in effectively managing data at the village level, in line with the Desa Cantik initiative and Indonesia One Data (SDI) program. The goal is to improve data accuracy and the effectiveness of village development planning. As a result, the statistical community, which also includes village officials, has shown increased capabilities in managing sectoral statistics and digitalizing data integrated with the Desa Cantik program. The village officials actively participated in this assistance, supported by the provincial and district BPS, who acted as facilitators. BPS provided training, monitoring, evaluation, and assistance in the preparation of program materials and outputs. One of the key outputs of this program is the creation of an infographic summarizing the statistics and potential of Bantar Village, covering demographic profiles, population density, and key commodities. This infographic serves as a visual communication tool that supports data-driven development planning. The program successfully established a strong foundation for better data management, supporting sustainable village development.